Progress in Research on Colorectal Cancer-Related Microorganisms and Metabolites - Han S; Zhuang J; Wu Y; Wu W; Yang X (Cancer Management and Research, 2020)
Shuwen Han,1 Jing Zhuang,2 Yinhang Wu,3 Wei Wu,4 Xi Yang1 1Department of Oncology, Huzhou Cent Hospital, Affiliated Cent Hospital HuZhou University, Huzhou 313000, People’s Republic of China; 2Graduate School of Nursing, Huzhou University, Huzhou 313000, People’s Republic of China; 3Graduate School of Second Clinical Medicine Faculty, Zhejiang Chinese Medical University, Hangzhou 310053, People’s Republic of China; 4Department of Gastroenterology, Huzhou Cent Hospital, Affiliated Cent Hospital HuZhou University, Huzhou 313000, People’s Republic of ChinaCorrespondence: Xi YangDepartment of Oncology, Huzhou Cent Hospital, Affiliated Cent Hospital HuZhou University, 198 Hongqi Rd, Huzhou, Zhejiang, People’s Republic of ChinaTel +8605722555650Email yangxi0601@hotmail.comWei WuDepartment of Gastroenterology Huzhou Cent Hospital, Affiliated Cent Hospital HuZhou University, 198 Hongqi Road, Huzhou, Zhejiang, People’s Republic of ChinaTel +8605722555650Email hchwuwei2018@126.comAbstract: Intestinal flora is an important component in the human body, which have been reported to be involved in the occurrence and development of colorectal cancer (CRC). Indeed, changes in the intestinal flora in CRC patients compared to those in control subjects have been reported. Several bacterial species have been shown to exhibit the pro-inflammatory and pro-carcinogenic properties, which could consequently have an impact on colorectal carcinogenesis. In this review, we summarize the current knowledge on the potential links between the intestinal microbiota and CRC. We illustrated the mechanisms by which intestinal flora imbalance affects CRC, mainly focusing on inflammation, microbial metabolites, and specific bacteria species. In addition, we discuss how a diet exhibits a strong impact on microbial composition and provides risks for developing CRC. Finally, we describe the potential future directions that are based on intestinal microbiota manipulation for CRC diagnosis and treatment.Keywords: intestinal flora, colorectal cancer, inflammation, microbial metabolites, diet